The Model for Promoting Cultural Tourism of Buddhists in the Mun River Basin Community Dansai District Loei Province - Chuaboonmee, Prakaymas; Chanthawan, Udorn; Piriyasuwat, Jaruchit (Journal of Dhamma for Life, 2026)
This study aims to (1) examine the cultural tourism potential of Buddhist communities in the Mun River Basin, (2) analyze existing tourism promotion processes, and (3) propose a community-appropriate model for cultural tourism enhancement. A qualitative research approach was employed, utilizing document review, field observation, and in-depth interviews with key stakeholders, including government officials, local administrators, monks, community leaders, entrepreneurs, and residents. The findings indicate that the area possesses rich cultural assets—such as the Bun Luang–Phi Ta Khon festival, Phra That Si Song Rak, significant temples, and local wisdom reflecting strong Buddhist identity. Despite this potential, current tourism management remains fragmented, particularly in information systems, public communication, and inter-organizational collaboration. The proposed promotion model includes developing activities aligned with traditional cultural calendars, designing integrated cultural routes, strengthening the roles of local leaders as cultural transmitters, and establishing a cultural learning center. This model supports sustainable cultural tourism development and helps preserve the unique identity of the Mun River Basin communities.